Kegiatan Bongkar Muatan Batu Bara Pada PLTU Tanjung Jati B Jepara: Sebuah Kajian Empiris Pada PT Anugerah Jaya Mandiri Tubanan Bangkit - Dani Eristian Pradana; Endah Fauziningrum (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
Ships is used in trading activities between islands in Indonesia. Discharge is one of the most important activities in trading. Loading and discharge activities include document preparation, preparation of discharge equipment, preparation of the required workforce, preparation for the discharge, preparation for the actual discharge and the completion of discharge activities. This study discusses preparation procedures for coal discharging and the process of the actual coal discharge by PT Anugerah Jaya Mandiri Tubanan Bangkit. The data collection methods used in this study were observation, interviews, and library research. In this study, we can find out about the documents in the process of coal discharge and the process of carrying out coal discharge. PT. Anugerah Jaya Mandiri Tubanan Bangkit Jepara collaborates with various parties involved in the cargo unloading process. The process that must be gone through is the stevedoring and cargodoring process or moving the coal after it is unloaded from the ship.